v.26 - "Keynes, John Maynard" (New Delhi, 2013)
Between the outbreak of war in 1939 and his death in April 1946, Keynes was closely involved in the management of Britain's war economy and the planning of the post-war world. This volume, the fifth of six dealing with this period, focuses on three aspects of his activities in planning the post-war world: the final stages of the discussions and negotiations that brought the International Monetary Fund and World Bank to birth at Bretton Woods and Savannah, the negotiations over commercial policy, and the discussions on reparations and the post-war treatment of Germany. On all of these subjects it contains Keynes's attempts to influence, often with success, the course of events in both Britain and America.
Keywords: Keynesianism